Best Answer

It is: -4x^2 +11x -6 equals (-4x+3)(x-2) when factored

Q: Is a Correct factorization of this trinomial -4x2 plus 11x-6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x2 + 36x + 81 = 3(x2 + 13x + 27)

-x2 + 2x + 48 = (x +6)(8 - x)

2x2 + 15x + 25 = (2x + 5)(x + 5)

x3 + 13x2 + 42x = x(x + 6)(x + 7).

2x2+9x+9 = (2x+3)(x+3) when factored

Related questions

It is: (x2 + 5x) (x + 8)

(2x+7)(x+7)

x(x + 9)(x + 5)

(-4x + 3)(x - 2)Apex :)!!

x(x + 4)(x + 6)

(x + 1)(x + 5)

2x2+21x+49 = (2x+7)(x+7)

2x2 + 15x + 25 = (2x + 5)(x + 5)

3x2 + 36x + 81 = 3(x2 + 13x + 27)

-x2 + 2x + 48 = (x +6)(8 - x)

-x2 + 2x + 48 = (-x - 6)(x - 8)

x3 + 13x2 + 42x = x(x + 6)(x + 7).